"Another Link in the Chain" Update State Policies and Practices for Case Management and Environmental Investigation for Lead-Poisoned Children - McLaine, Pat.; Gaitens, Joanna; National Center for Healthy Housing, Inc., Columbia, MD.; Alliance to End Childhood Lead Poisoning, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
This report details a national survey, conducted in 2000, to document changes since 1998 in policies and practices for case management and environmental investigation for lead poisoned children; the study also investigated the impact of the previous national survey in precipitating change. Participating in the survey were program directors or knowledgeable staff from all state programs, including the District of Columbia, and 19 local programs. Among the findings are that only 24 states require labs to report all blood lead levels (BLLs), not just elevated ones; there was an overall decline in reported numbers of children with elevated BLLs; only 14 states had developed linkages to enable health departments and Medicaid agencies to track screening among Medicaid beneficiaries; 20 states and 2 local programs are unable to provide minimal level case management services, and 25 state and 7 local programs are unable to meet current Centers for Disease Control guidelines for environmental investigations. Chapter 1 of the report is an executive summary of the methodology and findings of the study. Chapter 2 details the methodology and findings with recommendations made in four areas: (1) developing and maintaining an infrastructure for dealing with childhood lead poisoning, including developing a system of laboratory reporting, a system to identify new cases, and the ability to identify children enrolled in Medicaid; (2) availability of adequate resources for secondary prevention efforts, including reimbursement for case management and environmental investigation; (3) ability of Childhood Lead Poisoning Prevention Programs (CLPPPs) to assure follow-up care by following Centers for Disease Control recommendations for blood lead level triggers, by increasing dust testing, and incorporating case close-out criteria; and (4) changing practices since the last national survey, focusing on program self-evaluation. A list of abbreviations is appended to Chapter 2. Chapter 3 presents individual state and local progress reports, focusing on key indicators of a competent childhood lead poisoning prevention program. (KB)
Availability: Alliance to End Childhood Lead Poisoning, 227 Massachusetts Avenue, NE, Suite 200, Washington, DC 2002. Tel: 202-543-1147; Fax: 202-543-4466; e-mail: aeclp@aeclp.org; Web site: http://www.aeclp.org.
ERIC Note: For "Another Link in the Chain", see ED 441 614.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Caseworker Approach; Child Health; Children; Environmental Influences; Lead Poisoning; Medical Services; National Surveys; Prevention; Program Improvement; Public Health; Public Policy; Special Health Problems; Standards; American Academy of Pediatrics -- Case Management -- Centers for Disease Control GA -- Indicators -- Medicaid -- State Policy; Reports, Evaluative